The impact of violation type and presence of apology on purchase intention through perceived justice, trust and anger - Yücesal, Cengiz Emre (İstanbul Bilgi Üniversitesi, Lisansüstü Eğitim Enstitüsü)
In today’s competitive and reputation-sensitive marketplace, businesses are evaluated not only on their product and service quality but also on how they respond to crises. This study investigates the impact of marketing violations and crisis response strategies on consumer perceptions, emotions, and behavioral intentions. Specifically, it explores how the type of violation (internal vs. external) and the presence of an apology affect perceived justice and consumer trust. These, in turn, influence consumer anger and purchase intention. Grounded in attribution and justice theory, a conceptual model with seven hypotheses was developed. Internal violations are proposed to negatively affect perceived justice and trust, while an apology is expected to positively influence both. Reduced anger is predicted when justice and trust are perceived, ultimately leading to higher purchase intention. An experimental design was implemented through an A/B test using an online questionnaire. Participants were randomly assigned to crisis scenarios varying by violation type and apology presence. Measures included perceived justice, trust, anger, and purchase intention. Correlation and regression analyses were conducted to test the hypotheses. The findings aim to contribute to the crisis communication and consumer behavior literature by offering insights into how consumers process brand crises. Practically, the results provide guidance for brand managers on the strategic use of apology and message framing to mitigate reputational damage and maintain consumer loyalty.